Transcriptional and Histochemical Signatures of Bone Marrow Mononuclear Cell-Mediated Resolution of Synovitis - Menarim, Bruno C.; El-Sheikh Ali, Hossam; Loux, Shavahn C.; Scoggin, Kirsten E.; Kalbfleisch, Theodore S.; MacLeod, James N.; Dahlgren, Linda A. (Frontiers in Immunology, 2021)
Osteoarthritis (OA) may result from impaired ability of synovial macrophages to resolve joint inflammation. Increasing numbers of synovial macrophages through joint injection with bone marrow mononuclear cells (BMNC) induces lasting synovial inflammation resolution. To uncover mechanisms by which BMNC may affect resolution, in this study, differential transcriptional signatures of BMNC in response to normal (SF) and inflamed synovial fluid (ISF) were analyzed. We demonstrate the temporal behavior of co-expressed gene networks associated with traits from our previous in vivo and in vitro studies. We also identified activated and inhibited signaling pathways and upstream regulators, further determining their protein expression in the synovium of inflamed joints treated with BMNC or DPBS controls. BMNC responded to ISF with an early pro-inflammatory response characterized by a short spike in the expression of a NF-ƙB- and mitogen-related gene network. This response was associated with sustained increased expression of another gene network comprising known drivers of resolution (IL-10, IGF-1, PPARG, isoprenoid biosynthesis). This network was common to SF and ISF, but more highly expressed in ISF and. Similarly, most highly activated pathways in ISF included the super pathway of cholesterol biosynthesis and PPAR-γ signaling, with pro-resolving functional annotations that improve mitochondrial metabolism and deactivate NF-ƙB signaling. Higher expression of the PPAR-γ c0-activator 1-ɑ in synovium from inflamed joints treated with BMNC, and equivalent IL-1β staining between BMNC- and DPBS-treated joints, emphasize the intricate balance of pro- and anti-inflammatory mechanisms required for resolution. Combined, our data suggest that BMNC-mediated resolution is characterized by constitutively expressed homeostatic mechanisms, whose expression are enhanced following tissue damage. These mechanisms translate into macrophage proliferation optimizing their capacity to counteract inflammatory damage and improving their general and mitochondrial metabolism to endure oxidative stress while driving tissue repair. Such effect is largely achieved through the synthesis of several lipids that mediate recovery of homeostasis. Our study reveals candidate mechanisms by which BMNC provide lasting improvement in patients with OA and suggests further investigation on the effects of PPAR-γ signaling enhancement for the treatment of arthritic conditions.